2014
DOI: 10.3171/2013.12.spine12811
|View full text |Cite
|
Sign up to set email alerts
|

No association between excessive wound complications and preoperative high-dose, hypofractionated, image-guided radiation therapy for spine metastasis

Abstract: Object Radiation therapy is known to impair wound healing. Higher dose per fraction is believed to increase this risk. This study sought to quantify rates of wound complication in patients receiving preoperative conventionally fractionated radiotherapy (XRT) or high-dose hypofractionated image-guided radiation therapy (IGRT) for spinal metastasis, and to identify predictors of wound complication. Methods The records of 165 consecutive patients who underwent spine surgery for metastasis at Memorial Sloan–Kette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Of note, in this series, most patients underwent radiation therapy within 4 weeks of surgery. Preoperative or postoperative radiation within this window is generally considered to increase the risk of wound dehiscence and infection [44]. In general, at least 3 weeks are therefore required after open surgery before starting cEBRT to the area.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, in this series, most patients underwent radiation therapy within 4 weeks of surgery. Preoperative or postoperative radiation within this window is generally considered to increase the risk of wound dehiscence and infection [44]. In general, at least 3 weeks are therefore required after open surgery before starting cEBRT to the area.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past several years, there has been a transition to the use of stereotactic radiosurgery via high-dose, hypofractionated, image-guided radiation therapy, rather than conventional fractional radiotherapy. 20 A recent published study by Harel et al concluded that modern-day adjuvant stereotactic radiosurgery (single fraction) to the spine following surgery for metastasis allows high local control rates, but at the same time delivers less radiation to the wound. 18 Additional contemporary studies are needed to further evaluate this topic.…”
Section: Discussionmentioning
confidence: 99%
“…Durable tumor control has been shown with this therapy 7 along with low risk of complications such as hardware failure and wound infections. 20,21 The NOMS framework, 22 which consists of neurologic, oncologic, mechanical stability and systemic considerations, provides evidence-based guidance for treatment decisions in patients with spinal metastases. Patients with high-grade MESCC 23 and radioresistant tumors (ie, tumors that are known to be resistant to conventional external beam radiotherapy) require separation of the tumor from the thecal sac, in order to allow adequate SRS dosing to include the entire volume, including the epidural margin, while conforming to safety constraints to the spinal cord.…”
Section: Discussionmentioning
confidence: 99%